Clinical Profile of Impaired Hearing in Children with Autism Spectrum Disorder (ASD) at UGM Academic Hospital - Lestari, Ade Febrina; Sitaresmi, Mei Neni; Wibowo, Anton Sony; Sari, Shinta Kusumalarna; Ridhayanti, Firda (Rumah Sakit Akademik Universitas Gadjah Mada, 2024)
Background: Hearing tolerance is impaired in children with Autism Spectrum Disorder (ASD), which can affect social and academic functioning. This study aims to describe the clinical profile of hearing impairments in children with ASD and determine the prevalence of such impairments. Method: A cross-sectional study was conducted at Academic Hospital UGM on pediatric ASD patients aged 18 months to 12 years who underwent hearing exams like BERA (brain-evoked response auditory) and/or audiometry. ASD severity was assessed using the Childhood Autism Rating Scale (CARS) and a questionnaire on demographics and comorbidities, followed by BERA tests. Results: A total of 41 ASD children were obtained, with 31 children (76%) being boys and an average diagnosis age of 3.3 years (±1.3 SD). Hearing loss was suffered by 4 children (10%) and 37 children (90%) did not experience hearing loss. Sound sensitivity and degree of ASD correlated with head banging (p=0.01), and male gender correlated with hearing loss (P=0.006). CARS score was statistically associated with sound sensitivity (p=0.041) and degree of ASD (<0.001). Conclusion: Children diagnosed with ASD face an increased susceptibility to communication impairments which can be attributed to hearing impairments. This issue warrants particular attention in the context of ASD, highlighting the necessity for thorough screening of hearing capabilities.